NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU KUMPULAN CERPEN DIJAMIN BUKAN MIMPI: KUMPULAN CERITA SATIRIS DAN INSPIRATIF KARYA MUSMARWAN ABDULLAH - Vera Wardani; Salsa Bila; Nofiana S (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2026)
This study aims to describe the character education values contained in Dijamin Bukan Mimpi: Kumpulan Cerita Satiris dan Inspiratif by Musmarwan Abdullah. The research employed a qualitative approach using a descriptive method. The data source consisted of fifteen short stories included in the collection, while the research data comprised narrative excerpts, dialogues, and characters’ behaviours that reflected character education values. Data were collected through reading and note-taking techniques, and analysed by identifying, classifying, describing, and drawing conclusions regarding the character values found in the stories. The findings reveal a range of character education values, namely religiosity, honesty, responsibility, discipline, hard work, independence, democracy, communicativeness, peacefulness, social awareness, environmental awareness, curiosity, creativity, critical thinking, national spirit, patriotism, appreciation of achievement, and a love of reading. Among these, religiosity and responsibility were the most dominant values. The author conveys these values through satire, allegory, social symbolism, and life conflicts closely related to the realities of modern society. These findings indicate that the short stories in this collection have considerable potential to serve as a medium for character formation among readers.